Marx at the Arcade: Consoles, Controllers, and Class Struggle - MacDougall, Robert (Labour / Le Travail, 2020)
The article reviews the book, "Marx at the Arcade: Consoles, Controllers, and Class Struggle," by Jamie Woodcock.